NAVIGATING CHILDREN MENTAL HEALTH IN MY QUIET SHIP: A LACANIAN PSYCHOANALYTIC STUDY - Hayaa Azzahra Putri Riza; Resneri Daulay (Lire Journal (Journal of Linguistics and Literature), 2025)
This study aims to examine the mental health issues of Quinn, the main character in the picture book My Quiet Ship (2018) by Hallee Adelman. Quinn’s various traumatic experiences are analyzed through Jacques Lacan’s psychoanalytic stages: the real, the imaginary, and the symbolic. A descriptive qualitative method with a psychoanalytic approach is employed. The primary data consist of narrative and visual elements from the book. Findings reveal that the real phase is reflected in Quinn’s trauma caused by his parents’ quarrels. His creation of an imaginary world illustrates the imaginary phase, where he builds a sense of safety and comfort through fantasy. The symbolic phase emerges as Quinn begins to express his fears to his parents. Moreover, the quiet ship in Quinn’s imagination functions as an objet petit a, symbolizing lost security and inner peace. This study confirms that My Quiet Ship not only portrays children’s traumatic experiences but also highlights the crucial role of imagination ang language in identity formation in line with Lacanian theory.